Activities of potassium and sodium ions in rabbit heart muscle (The Rockefeller University Press, 1975)
Activities (a) of intracellular K and Na in rabbit ventricular papillary muslces were determined with cation-selectivve glass microelectrodes and concentrations (C) were estimated with flame photometry. The CK and aK of the muscles were 134.9 +/- 3.1 mM (mean value +/- SE) and 82.6 mM, respectively, at 25 degrees C. The corresponding CNa and aNa were 32.7 +/- 2.7 and 5.7, respectively. The apparent intracellular activity coefficients for K (gammaK) and Na (gammaNa) were 0.612 and 0.175, respectively. Similar results were obtained at 35 +/- 1 degree C. gammaK was substantially lower than the activity coefficient (0.745) of extracellular fluid (Tyrode's solution), which might be expected on the basis of a different intracellular ionic strength. gammaNa was much lower than that of extracellular fluid, and suggest that much of the Na was compartmentalized or sequestered. For external K concentrations greater than 5 mM, the resting membrane potentials agreed well with the potential differences calculated from the K activity gradients across the cell membrane as a potassium electrode. These results emphasize that potassium equilibrium potentials in heart muscle should be calculated by activities rather than concentrations.